Indonesia And Germany Bilateral Cooperation Towards Renewable Energy Transition Through Clean, Affordable and Secure Energy (Case) - Hariyadi, Firsty Afrilia; Suryadipura, Dadan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The Russian-Ukraine conflict has caused a threat to energy security that encourages the Indone- sian government in pursuing transition toward renewable energy. To actualize this transition to- wards renewable energy, Indonesia invites external actors to collaborate, such as Germany through Clean, Affordable, and Secure Energy (CASE) programme. This article aims to inform and raise awareness towards Indonesian government efforts in tackling energy security threats through bilateral cooperation with Germany through the CASE programme. This research fo- cuses on how CASE programme assists Indonesia in objectifying transition towards renewable energy and its attempt to overcome various challenges of energy transition, such as low invest- ment rate towards renewable energy and ineffective budget allocation based on the concept of energy security. This article uses a descriptive-qualitative research design. The analysis showed that Indonesia-Germany bilateral cooperation through CASE programme has helped Indonesia to maximize renewable energy potential through research assistance, public participation en- couragement, discussions between stakeholders, and assistance in technical matters. This article concludes that CASE programme has actually offered resolutions towards Indonesia’s problems in renewable energy transition, such as: encouraging the ratification of the Presidential Decree of NRE to enhance investment in renewable energy sector and providing research assistance in the development of renewable energy technology. However, the Indonesian government's de- layed response towards the Presidential Decree of NRE is a challenge to CASE Programme implementation in Indonesia.